Linking corporate reputation and shareholder value using the publication of reputation rankings - Sven Tischer; Lutz Hildebrandt (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
Good corporate reputation is seen as one of the most valuable assets. It is believed to cause a multitude of favorable impacts within different stakeholder groups. As a consequence, a multitude of studies analyzed the relationship between corporate reputation and financial performance. However, the most of them raised the question of causation due to their methodology. In order to isolate the impact of corporate reputation on financial performance, some authors had conducted event studies, but without any success. Therefore, this study provides a comprehensive theoretical background, why reputation has to affect financial performance. According to this theory, two event studies are conducted to analyze the impact of publishing reputation rankings of the German Manager Magazine from 1998 to 2008 on share prices. As expected, we find positive or negative announcement effects regarding upgraded or respectively downgraded companies. Consequently, investors gain new information from the published rankings (increase or decrease in reputation) to adjust share prices.
Keywords: M14; M31; G14; G11; C12; C13; 330; corporate reputation; reputation ranking; financial performance; shareholder value; event study; portfolio study; Firmenimage; Bewertung; Shareholder Value; Börsenkurs; Theorie; Event Study; Deutschland